2018
DOI: 10.3892/mmr.2018.9372
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑675‑3p promotes esophageal squamous cell cancer cell migration and invasion

Abstract: Esophageal cancer ranks fourth in cancer-associated mortality in China and the incidence of esophageal adenocarcinoma has risen dramatically over the past two decades. MicroRNA (miRNA/miR) serves a pivotal role in human cancer cell growth, invasion and migration. MiR-675-3p is highly expressed in esophageal squamous cell cancer (ESCC) tissues, and may have an influence on ESCC cell migration and invasion. ESCC tumor tissue samples from 35 patients were profiled. MiR-675-3p expression was confirmed by reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…MiRNAs could emerge as significant regulators in tumor initiation and progression [25]. Extensive reports have unveiled a series of dysregulated miRNAs in ESCC [26,27]. MiR-3612 is a novel miRNA that has not been studied in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs could emerge as significant regulators in tumor initiation and progression [25]. Extensive reports have unveiled a series of dysregulated miRNAs in ESCC [26,27]. MiR-3612 is a novel miRNA that has not been studied in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-146a, miR-133b, miR-106b-3p, miR-219-5p, miR-206, miR-384, miR-455-5p, miR-128, miR-145-3p/5p, miR-10b-3p, miR-874-3p, miR-10a, miR-365, miR-301a, miR-6775-3p, miR-139-5p, miR-516b, miR-449a-5p, miR-125b, miR-433-3p, miR-370, miR-133b, miR-30a-3p/5p, miR-34a, miR-196a, and miR-125b-5p have been shown to act as tumor suppressors by inhibiting ESCC cell proliferation, promoting apoptosis by directly targeting oncogenes, or antagonizing pro-cancer signaling pathways [29,33,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][54][55][56][57][58][60][61][62][63]110,133]. In contrast, pro-oncogenes such as miR-141, miR-21, miR-10b-3p, miR-424, miR-675-3p, miR-543, miR-135, miR-23b-3p, miR-502, miR-21-5p, and miR-548k have been reported to play contrasting roles in promoting cell proliferation or suppressing apoptosis in ESCC [47,[64][65][66][67][68][69][70][71][72][73]. Overall, the roles of miRNAs in cell proliferation and apoptosis can be crucial in ESCC pathogenesis.…”
Section: Non-coding Rnas Regulate Cell Proliferation and Apoptosis Dumentioning
confidence: 99%
“…20 Extensive studies have shown that a plethora of miRNAs are dysregulated in ESCC, and the deregulated miRNAs are implicated in the pathogenesis and progression of ESCC by modulating multiple pathological processes. [21][22][23] Therefore, in-depth research into the regulatory roles of miRNAs in ESCC may provide novel opportunities for identifying effective techniques for the diagnosis and therapy of patients with ESCC.…”
Section: Introductionmentioning
confidence: 99%